The Problem of Vocabulary in Indonesian and Malaysian from Malaysia Students at UIN Sunan Ampel Surabaya - Lukman Fahmi; Amiatun Nuryana (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2023)
Students from Malaysia who study in Indonesia are mostly Malay speakers in their home countries, however they have trouble understanding Indonesian in common word forms. Especially when students produce scholarly papers, theses, or other academic assignments. This latest study investigates the Indonesian language comprehension problem among Malaysian students at UIN Sunan Ampel Surabaya. This research focuses on uncovering issues related to what problems they experience and the factors that cause these problems to arise. The qualitative descriptive method was applied in this study through observation and interviews. This study discovered that the key to Malaysian students' language proficiency is their comprehension of both spoken and written language. The factors that make them experience problems in understanding Indonesian are derived from internal and external factors (their adapting environment). External influences have a significant impact on Malaysian students' ability to learn Indonesian verbally and in writing.